Female labor supply and parental leave benefits: the causal effect of paying higher transfers for a shorter period of time - Annette Bergemann; Regina T. Riphahn (Center for Economic Studies and ifo Institute (CESifo), 2009)
We study the labor supply effects of a change in child-subsidy policy designed to both increase fertility and shorten birth-related employment interruptions. The reform yields most of the intended effects.
Keywords: J13; J21; 330; Female labor supply; fertility; child subsidy; parents money; Erziehungsurlaub; Wirtschaftspolitische Wirkungsanalyse; Frauenerwerbstätigkeit; Arbeitsangebot; Deutschland